Issues Around Aligning Theory, Research and Practice in Social Work Education - Shokane, Allucia Lulu; Makhubele, Jabulani; Blitz , Lisa V. (Knowledge Pathing: Multi-, Inter- and Trans-Disciplining in Social Sciences Series, 2018)
Issues Around Aligning Theory, Research and Practice in Social Work Education provides a reflection on social work education with a slant towards an Afrocentric approach, aiming to facilitate strong reflective thinking and to address local realities about social work education on the African continent as well as in broader global contexts. This volume focuses on issues around aligning theory, research and practice in social work education. A significant contribution is made here to the scholarly understanding of opportunities to sustain the academic discourse on social work education. Social work as a profession and a social science discipline is dynamic, and it ought to meet the challenges of the realities of the societies in which it serves, given the history of the changing society of South Africa from apartheid to democracy. Over the years, social work education and training has undergone tremendous curricular changes with the enactment of the White Paper for Social Welfare and the national review, respectively, by the South African Council for Social Services Professions (SACSSP) and the Council on Higher Education (CHE) for the re-accreditation of all Bachelor of Social Work (BSW) programmes in South Africa fulfilling the prescripts of the Higher Education Act (No. 101 of 1997, as amended) and Social Service Professions Act (No. 110 of 1978). It is worth mentioning that the curricular changes will also continue with the current reviewing of Social Service Professions Act (No. 110 of 1978), as amended, which is underway in South Africa. This book is really ground-breaking! The Afrocentric perspective on social work practice contributes to the current discourse on decolonisation of social work teaching and practice. From a methodological perspective, the book is premised on multi-, inter- and trans-disciplining in social sciences. It covers aspects of social work education and practice through research (narrative, qualitative, African methodology, secondary data analysis, etc.), engendering values and ethics, report writing, supervision in fieldwork as well as exchange programmes and international service-learning, addressing a number of concepts such as cultural competency, cultural awareness and sensitivity are addressed.